ENDOTHELIUM AND CARDIOPROTECTIVE EFFECTS OF HMG-CO-A-REDUCTASE IN COMBINATION WITH L-ARGININE IN ENDOTHELIAL DYSFUNCTION MODELING - Tatiana Denisyuk; Galina Lazareva; Vladimir Provotorov; Tatyana Pokrovskaya (Belgorod National Research University, 2016)
Using the combined application of L-arginine with HMG-Co-A reductase inhibitors simvastatin, atorvastatin, rosuvastatin and nanoparticulated rosuvastatin on the background of modeling of sepsis-induced disease through the introduction of strain 603 Staphylococcus aureus shows endotelio- and cardioprotective effects, manifesting itself in preventing the proliferation of endothelial dysfunction coefficient (CED), adrenoreactivity, maintenance of myocardial reserve and the normalization of biochemical markers values (Total NO, eNOS expression, C-reactive protein, IL-6, TNF). In this case, the combined therapy was so effective that the values obtained thereunder did not differ from those obtained from control animals.